The wolf and the watchman : a novel - Natt och Dag, Niklas, 1979- (Atria Books, 2019)
One morning in the autumn of 1793, watchman Mikel Cardell is awakened from his drunken slumber with reports of a body seen floating in the Larder, once a pristine lake on Stockholm<U+2019>s Southern Isle, now a rancid bog. Efforts to identify the bizarrely mutilated corpse are entrusted to incorruptible lawyer Cecil Winge, who enlists Cardell<U+2019>s help to solve the case. But time is short: Winge<U+2019>s health is failing, the monarchy is in shambles, and whispered conspiracies and paranoia abound. Winge and Cardell become immersed in a brutal world of guttersnipes and thieves, mercenaries and madams. From a farmer<U+2019>s son who is lead down a treacherous path when he seeks his fortune in the capital to an orphan girl consigned to the workhouse by a pitiless parish priest, their gruesome investigation peels back layer upon layer of the city<U+2019>s labyrinthine society. The rich and the poor, the pious and the fallen, the living and the dead<U+2014>all collide and interconnect with the body pulled from the lake.